DNMT1 and p38γ are inversely expressed in reactive non‐metastatic lymph nodes burdened with colorectal adenocarcinoma. Issue 1 (29th June 2020) - Zhang, Xu Hannah; Yin, Zhirong; Zhang, Aimin; Pillai, Raju; Armstrong, Brian; Rosen, Steven T
Abstract: Lymph nodes are important front‐line defense immune tissues, which also act against inflammatory diseases and cancer. Lymph nodes undergo extensive upheavals within newly formed germinal centers (GCs) when exposed to antigens, the molecular mechanisms of which remain elusive. Recently, p38γ was identified as an important target for multiple cancers, including cutaneous T‐cell lymphoma (CTCL). We previously observed that p38γ is overexpressed in CTCL versus normal cells, but it is not clear if p38γ is expressed in B or T lymphocytes of GCs of patients in response to a stress such as cancer. Therefore, in this study, we obtained non‐metastatic reactive lymph nodes adjacent to cancer lesions (colorectal adenocarcinoma), then performed multicolor immunohistochemical staining for p38γ and other relevant markers. We observed for the first time that p38γ was expressed in the light zone of activated B cells and T helper cells in GCs, whereas DNA‐methyltransferase 1 (DNMT1), a marker for GC B cells, was highly expressed in centrocytes and in the dark zone of GCs. This inverse relationship suggests a novel function for p38γ in T cells that cross‐talk to B cells in response to stress.